A Study on Heavy Metal Materials in Cosmetic Makeup Concealers (Medico Legal Update, 2019)
Background/Objective: This paper aimed to select low-priced and high riced concealer products sold inKorea to analyze the inorganic materials in these cosmetic products and to investigate whether any heavymetal materials harmful to humans are present in them.Method: The inorganic materials and heavy metal materials in the concealer cosmetics products wereobserved with a scanning electron microscope and the component elements were analyzed using energydispersion spectroscopy.Findings: Both the low- and high-priced concealer products used for this study mainly contained silica,titanium dioxide, and iron oxide. The study found that the high-priced concealer products did not containheavy metal materials harmful to humans but the low-priced concealer products contained the radioactivematerial technetium. When cosmetics containing this radioactive material are applied over a long period oftime adverse health and cosmetic effects may develop.Improvements/Applications: Not only stones and soil in nature but also metals in water may be mixedinto the base materials used to manufacture cosmetics. High-purity base materials must be used to producehigh-quality cosmetics and a thorough quality control process must be applied to the manufacturing processto prevent foreign materials from contaminating cosmetics products.